Primary analysis and research on code-based schemes of electronic digital signature and public-key cryptosystems from NIST PQC - Kiian, A.S.; Lutsenko, M.S.; Kuznetsov, A.A. (Radiotekhnika, 2018)
The code-based schemes of electronic digital signature and public-key cryptosystems, submitted to the contest of post-quantum cryptoalgorithms NIST PQC are considered. The general characteristics of the algorithms are give and basic properties and parameters are estimated. The comparative analysis of the electronic digital schemes and public-key cryptosystems is carried out according to the criteria of speed and length of the main cryptographic parameters.